PERSIAPAN TROLLEY CART OLEH ROOM ATTENDANT PADA DEPARTEMEN HOUSEKEEPING FOX HARRIS HOTEL PEKANBARU - Fiqri, Nurul; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Carrying out trolley cart preparation by room attendants in the housekeeping department is a key element in hotel operations which functions to maintain the cleanliness and comfort of rooms for guests. At Fox Harris Hotel Pekanbaru, this preparation is an integral part of the standard of service offered to guests. With increasing demands for service quality and guest satisfaction, it is important to ensure that every aspect of housekeeping operations, including trolley cart preparation, runs optimally. Trolley carts are the main tool used by room attendants to carry cleaning supplies and equipment to each room. Proper and efficient preparation of the trolley cart ensures that the room attendant has everything needed to clean and tidy the room quickly and without interruption. This not only improves work efficiency but also minimizes the time required to clean each room, so more rooms can be prepared for guests in less time. The purpose of this research is to find out and analyze the implementation of cleaning cart preparations (Trolley Cart) in the housekeeping department of the Fox Harris Hotel Pekanbaru and to find out and analyze the obstacles to implementing cleaning cart preparations (Trolley cart) in the housekeeping department of the Fox Harris Hotel Pekanbaru. This research uses direct observation methods and interviews with housekeeping staff and hotel management. The data collected was analyzed qualitatively to get an in-depth picture of how the trolley cart preparation was carried out and its implications for operations and guest satisfaction. Standard Operating Procedures (SOP), Room attendants at the Fox Harris Hotel Pekanbaru follow the SOP that has been set in preparing the trolley cart. The results of this research show that the implementation of trolley cart preparation by room attendants at the Fox Harris Hotel Pekanbaru has been carried out in accordance with the established SOP. Room attendant work efficiency increases, and guest satisfaction is well maintained. Proper trolley cart preparation is an important factor in ensuring quality service and efficient housekeeping operations. The recommendations provided include regular training for housekeeping staff and regular evaluation of existing procedures to ensure the quality of trolley cart preparation and room service is maintained. In this way, Fox Harris Hotel Pekanbaru can continue to maintain and improve their service standards, which ultimately increases guest satisfaction and loyalty. Keywords : trolley cart, room attendant, housekeeping